Malonic acid suppresses lipopolysaccharide-induced BV2 microglia cell activation by inhibiting the p38 MAPK/NF-κB pathway. Issue 2 (4th March 2021) - Lee, Hana; Jang, Jun-Ho; Kim, Seok-Jun
ABSTRACT: An inflammatory reaction caused by the activation of microglia in the brain can lead to neurodegeneration and cause diseases, such as Alzheimer's and Parkinson's disease. The regulation of inflammation can aid in preventing the development of neurodegenerative disease. Malonic acid has a variety of biological activity. The effects of malonic acid on microglia are not currently well known. Therefore, in this study, we investigate the effects of inflammation of malonic acid in BV2 microglia cells. As a result, we demonstrated that malonic acid on LPS-treated microglia decreased pro-inflammatory responses and mechanisms of the p38 MAPK/NF-κB pathway. Inflammatory mediators significantly decreased the LPS-induced production of nitric oxide and reactive oxygen species. Pro-inflammatory cytokines of IL-6 suppressed gene expression. In addition, the protein expression of NF-κB decreased at the nucleus, as did the protein expression of activated phosphorylated IκB-α, which is an NF-κB regulator-related protein. The expression of phosphorylated p38, a mediator of inflammatory cytokines, was regulated. Therefore, our results indicate that malonic acid has anti-inflammatory effects and may be a potential therapeutic candidate for neuroinflammatory diseases.